Manejo comportamental em sala de aula para redução de comportamentos de desatenção e hiperatividade: orientação ao professor e implementação de guia de intervenção - Siqueira, Alisson Rogério Caetano de (2015)
The Attention Deficit Hyperactivity Disorder (ADHD) is described by the DSM-5 as a persistent pattern of inattention and / or hyperactivity-impulsivity that interferes with the functioning or development. ADHD have their signals observed in at least two of child living environments (home and school mostly). The disorder s prevalence is estimated in 5% of children. The children's school development is frequently affected by the disorder. This study aims to analyze the effects of behavioral management procedures in the classroom, in order to reduce behaviors of inattention and hyperactivity, using an intervention guide by the teacher. This work gone along with 64 students, from 6 to 12 years old, students of the 2nd and 4th year of a Center of Entire Education of Curitiba, consisting of 4 classes distributed two in an Experimental Group (EG) and two a Control Group (GC). The behavioral profile was assessed, using the CBCL/6-18 for parents and the TRF/6-18 for teachers that were applied before and after the intervention, along with a teacher's observation protocol with targets characteristic behaviors of the ADHD signs. The intervention guide was developed in previous works according to the basic principles of behavior analysis, was implemented with the classes through the teacher in a total of 28 weeks. The implementation guide was well accepted by the teachers who filled the weekly record in a Checklist on its implementation and participated in weekly support meetings. It was observed by teachers a reduced frequency behavior of inattention and hyperactivity in students in the classroom, through the responses of teachers to TRF/6-18 and the observation protocol, and also reported by parents in filling the CBCL/6-18.